Evaluación de la intensidad del campo magnético en la línea de distribución Chone-Bolívar y sus riesgos físicos en la salud del trabajador - Calderón Zambrano, Juan Ramón (2025)
The objective of this research was to evaluate the intensity of the magnetic field produced by high-voltage power lines along the Chone-Bolívar distribution line and its physical health risks for electrical sector workers. A descriptive-statistical approach was applied as the methodology, allowing for the collection of detailed information and the acquisition of knowledge about the magnetic field and its impact on worker safety and health. The georeferencing technique was used to establish sampling points along the line and to create specific maps. To measure the frequency range, the Triple Axis Radio Frequency (RF) Digital Field Strength Meter EMF was employed, along with a characterization form to identify the intensity and frequency of magnetic field exposure in the distribution line. Once the data was collected, statistical graphs were used for comparison, and a survey was applied to determine the duration of radiation exposure and knowledge of its effects. Finally, a Labor Risk Prevention Plan was developed based on the logical framework matrix proposed by Ika and Lytvynov, through which physical risks were identified and qualified to mitigate and reduce their impact, creating a safer work environment. It was concluded that there is indeed a relationship between exposure levels and the established limits, identifying the main physical risks in the electrical sector within the study area as temperature, vibrations, radiation, noise, and thermal load.